Systematic review of N-acetylcysteine in the treatment of addictions - Asevedo, Elson de Miranda [UNIFESP] (2014)
Objective: To conduct the first systematic literature review of clinical trials of N-acetylcysteine (NAC) for the treatment of substance abuse disorders and addictive behaviors. Methods: A search of the MEDLINE, Embase and PsycINFO databases was conducted. The inclusion criteria for the review were clinical trials that used NAC in the treatment of a disorder related to substance use and/or addictive behaviors, limited to texts in English, Spanish, or French. The selected studies were evaluated with respect to type of trial, sample size, diagnostic input, intervention, length of follow-up, outcome variables, and results. Results: Nine studies analyzing a total of 165 patients met the eligibility criteria and were included in qualitative analysis. These studies evaluated the role of NAC in cocaine dependence (three studies), cannabis dependence (two studies), nicotine dependence (two studies), methamphetamine addiction (one study), and pathological gambling (one study). Five of these trials were double-blind, randomized, and placebo-controlled. Conclusions: The studies analyzed suggest a potential role for NAC in the treatment of addiction, especially of cocaine and cannabis dependence. These results are concordant with the hypothesis of the involvement of glutamatergic pathways in the pathophysiology of addiction.